Price and Product Quality as Determinants of Purchasing Decisions: A Case Study on Mrs. Ida’s Potato Chips - Muhammad Akbar Al-Asyari; Asri Solihat; Lindayani . (Entrepreneurship Faculty, Universitas Garut, 2025)
This study aims to find out and analyze the influence of price and product quality on consumer purchase decisions of